2013
DOI: 10.1159/000351867
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glia in the Regulation of Gonadotropin-Releasing Hormone Neuronal Activity and Secretion

Abstract: Gonadotropin-releasing hormone (GnRH) neurons are the final common pathway for the central control of reproduction. The coordinated and timely activation of these hypothalamic neurons, which determines sexual development and adult reproductive function, lies under the tight control of a complex array of excitatory and inhibitory transsynaptic inputs. In addition, research conducted over the past 20 years has unveiled the major contribution of glial cells to the control of GnRH neurons. Glia use a variety of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 110 publications
3
49
1
1
Order By: Relevance
“…), including the ependymoglial cell tanycytes . Previous studies have shown the importance of the plastic interaction between tanycytes, endothelial cells and GnRH varicosities in the regulation of the HPG axis function. The present data suggest that such neurone/glia/vascular interactions are influenced by the metabolic status of animals affects the HPG axis.…”
Section: Discussionsupporting
confidence: 64%
“…), including the ependymoglial cell tanycytes . Previous studies have shown the importance of the plastic interaction between tanycytes, endothelial cells and GnRH varicosities in the regulation of the HPG axis function. The present data suggest that such neurone/glia/vascular interactions are influenced by the metabolic status of animals affects the HPG axis.…”
Section: Discussionsupporting
confidence: 64%
“…There is now a growing body of evidence indicating that cell-cell interactions involving nonneuronal cells such as vascular endothelial cells, astrocytes and specialized ependymoglial cells named tanycytes, which ensheathe the terminals of GnRH neurons, might be of critical importance in the regulation of GnRH secretion [123,124,125,126] (fig. 4a).…”
Section: Semaphorins and Neuroglial Plasticity In The Adult Hypothalamentioning
confidence: 99%
“…R esearch over many years has indicated that a wide variety of classical neurotransmitters, neuropeptides, and other signaling molecules can modulate the activity of GnRH neurons to control gonadotropin secretion (1,2). Even though some transmitters, such as kisspeptin, are widely acknowledged as being of critical importance to GnRH neuron behavior, the functional hierarchy of most inputs remain unknown.…”
mentioning
confidence: 99%